Posterior tibial nerve schwannoma in a multiple myeloma patient: A case report. (April 2019) - Daniel, Michael; Waters, David; Chen, Chaoyang; Brouyette, Nicole
We report the case of a 61-year-old man with sharp pain, tender mass at the left lower one-third posterior tibial region. The patient has a 10-year history of multiple myeloma and related chemotherapy. A positron emission tomography computed tomography and magnetic resonance imaging indicated the suspect of a posterior tibial nerve tumor. En bloc resection of the tumor was performed under guidance of nerve stimulator without resecting nerve trunk. Active nerve was reserved without any neuropathic pain. Histology revealed the presence of a peripheral schwannoma. In conclusion, the tibial nerve schwannoma appeared to be a whole nerve mass, but meticulous dissection showed that this tibial nerve schwannoma was a well-encapsulated tumor and can be separated from the nerve trunk with active nerve fibers reserved. Removal of the tumor made patient free of pain and asymptomatic after surgery. The level of clinical evidence is 4.